TRANSDISCIPLINARY REPORTING OF INFORMATION WITH INTERACTIVE DOCUMENTS - Mintser, O. P.; Pryhodnyuk, V. V.; Stryzhak, O. Ye.; Shevtsova, O. M. (Medical Informatics and Engineering, 2018)
Theoretical generalizations and possibilities of practical use of ontology of knowledge in public health, in particular in diagnosis and choice of a method of treatment for diseases of the gastrointestinal tract in children, are investigated. It is shown that the consequence of the existence of a homomorphism between the primary structure of the text and the structure of information from it highlights the possibility of constructing a specialized structure designed to work not with ontology objects but with lexemes of the primary structure. The interactive document (Tsn,NS') built on its basis can be used to form an arbitrary network information system in the object plane.